2020
DOI: 10.34035/jk.v12i1.530
|View full text |Cite
|
Sign up to set email alerts
|

GEJALA DEPRESI POSTPARTUM MEMPENGARUHI KEBERHASILAN ASI EKSKLUSIF : Sistematik Literatur Riview

Abstract: Air Susu Ibu (ASI) merupakan satu-satunya makanan yang sempurna dan terbaik bagi bayi karena mengandung unsur-unsur gizi yang dibutuhkan untuk pertumbuhan dan perkembangan bayi yang optimal. Namun ada beberapa penyebab ibu tidak memberikan ASI secara eksklusif seperti tidak mendapatkan dukungan dari suami/keluarga, penghasilan, usia, pendidikan yang menyebabkan terjadinya depresi postpartum sehingga menghambat proses laktasi. Tujuan penelitian untuk menyimpulkan dan memeriksa literature (examine literature) ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
1
1
0
Order By: Relevance
“…The results of statistical tests also obtained a p-value of <0.003. Therefore, it can be concluded that there is a significant relationship between physical exercise and postpartum depression (Arami et al, 2020;Gustiani et al, 2022). This is in line with the literature that physical exercise during pregnancy, including yoga and pregnancy exercise, can reduce anxiety about childbirth and reduce postpartum depression symptoms.…”
Section: Discussionsupporting
confidence: 85%
“…The results of statistical tests also obtained a p-value of <0.003. Therefore, it can be concluded that there is a significant relationship between physical exercise and postpartum depression (Arami et al, 2020;Gustiani et al, 2022). This is in line with the literature that physical exercise during pregnancy, including yoga and pregnancy exercise, can reduce anxiety about childbirth and reduce postpartum depression symptoms.…”
Section: Discussionsupporting
confidence: 85%
“…16 Likewise, the results of research in Buleleng Regency prove that the age of mothers too young and too old as risk factors for failure to breastfeed exclusively, the age of mothers less than 20 years or more than 35 years increases the risk of failure to breastfeed by 1.83 times. 43 The age of the first mother giving birth greatly determines maternal health because it is related to the conditions of pregnancy, childbirth, and postpartum, as well as how to care for and breastfeed her baby. Mothers younger than 20 years old are still immature and not physically and socially ready to face pregnancy, childbirth, and breastfeeding of the baby.…”
Section: Discussionmentioning
confidence: 99%